Energy taxation and competitiveness: Special provisions for business in Germany's environmental tax reform - Michael Kohlhaas (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
Environmental taxation very often comprises special provisions for parts of the business sector in order to attenuate effects on competitiveness of emissionintensive activities. This paper discusses motives, alternative designs and criteria for the evaluation of such safeguards and analyzes if such provisions can reconcile environmental and economic objectives. It looks at theoretical aspects as well as practical issues of implementation and evaluates special provisions that have been discussed or implemented in the framework of the environmental tax reform (ETR) introduced in Germany in 1999. This reform is characterized by two features: Firstly, it aims at the reduction of greenhouse gases and thus at a global environmental problem. Secondly, environmental taxes are embedded in the framework of a revenue-neutral tax reform, where the additional tax revenue is recycled to the tax payers by a reduction of social security contributions. The reform should finance ?non-insurance-related benefits? of the pension insurance system in order to reduce labor costs and spur employment.
Keywords: H23; Q28; 330; environmental taxes; competitiveness; tax shift; Ökosteuer; Steuerreform; Energiesteuer; Steuerbegünstigung; Verarbeitendes Gewerbe; Steuerbelastung; Internationaler Wettbewerb; Deutschland